Longitudinal Dynamics of the Neutralizing Antibody Response to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection - Wang, Kai; Long, Quan-Xin; Deng, Hai-Jun; Hu, Jie; Gao, Qing-Zhu; Zhang, Gui-Ji; He, Chang-Long; Huang, Lu-Yi; Hu, Jie-Li; Chen, Juan; Tang, Ni; Huang, Ai-Long (Clinical infectious diseases, 2021)
Coronavirus disease 2019 (COVID-19) is a global pandemic with no licensed vaccine or specific antiviral agents for therapy. Little is known about the longitudinal dynamics of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-specific neutralizing antibodies (NAbs) in patients with COVID-19.BACKGROUNDCoronavirus disease 2019 (COVID-19) is a global pandemic with no licensed vaccine or specific antiviral agents for therapy. Little is known about the longitudinal dynamics of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-specific neutralizing antibodies (NAbs) in patients with COVID-19.Blood samples (n = 173) were collected from 30 patients with COVID-19 over a 3-month period after symptom onset and analyzed for SARS-CoV-2-specific NAbs using the lentiviral pseudotype assay, coincident with the levels of IgG and proinflammatory cytokines.METHODSBlood samples (n = 173) were collected from 30 patients with COVID-19 over a 3-month period after symptom onset and analyzed for SARS-CoV-2-specific NAbs using the lentiviral pseudotype assay, coincident with the levels of IgG and proinflammatory cytokines.SARS-CoV-2-specific NAb titers were low for the first 7-10 days after symptom onset and increased after 2-3 weeks. The median peak time for NAbs was 33 days (interquartile range [IQR], 24-59 days) after symptom onset. NAb titers in 93.3% (28/30) of the patients declined gradually over the 3-month study period, with a median decrease of 34.8% (IQR, 19.6-42.4%). NAb titers increased over time in parallel with the rise in immunoglobulin G (IgG) antibody levels, correlating well at week 3 (r = 0.41, P < .05). The NAb titers also demonstrated a significant positive correlation with levels of plasma proinflammatory cytokines, including stem cell factor (SCF), TNF-related apoptosis-inducing ligand (TRAIL), and macrophage colony-stimulating factor (M-CSF).RESULTSSARS-CoV-2-specific NAb titers were low for the first 7-10 days after symptom onset and increased after 2-3 weeks. The median peak time for NAbs was 33 days (interquartile range [IQR], 24-59 days) after symptom onset. NAb titers in 93.3% (28/30) of the patients declined gradually over the 3-month study period, with a median decrease of 34.8% (IQR, 19.6-42.4%). NAb titers increased over time in parallel with the rise in immunoglobulin G (IgG) antibody levels, correlating well at week 3 (r = 0.41, P < .05). The NAb titers also demonstrated a significant positive correlation with levels of plasma proinflammatory cytokines, including stem cell factor (SCF), TNF-related apoptosis-inducing ligand (TRAIL), and macrophage colony-stimulating factor (M-CSF).These data provide useful information regarding dynamic changes in NAbs in patients with COVID-19 during the acute and convalescent phases.CONCLUSIONSThese data provide useful information regarding dynamic changes in NAbs in patients with COVID-19 during the acute and convalescent phases.